Experiences of adolescents seropositive for HIV/AIDS: a qualitative study - Eliana Galano; Egberto Ribeiro Turato; Philippe Delmas; José Côté; Aida de Fátima Thomé Barbosa Gouvea; Regina Célia de Menezes Succi; Daisy Maria Machado (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: Explore the meanings attributed by young individuals about "living as an adolescent with HIV" in a group of patients that acquired the infection at birth and the elements involved with the adherence to antiretroviral treatment. Methods: Qualitative study, involving 20 subjects (aged 13-20 years), followed at services specialized in the treatment of pediatric AIDS in São Paulo, Brazil. Semi-structured interviews were carried out of which script consisted of questions about their personal histories, experiences and difficulties they must face while living with HIV/AIDS. Results: Being "normal" and "different" were central issues voiced by the participants. However, a normal life situation is guaranteed by being responsible with one's health, the condition that the diagnosis be kept secret and concerns about HIV transmission and dissemination to a sexual partner. The answers about treatment show that adherence is a dynamic process and involves moments of greater or lesser interest in relation to care for one's health. The adolescents have plans and projects and although HIV is considered a stressor, positive perspectives for the future prevailed. Conclusions: To live as an adolescent with HIV involves subtle dimensions that need to be recognized and legitimized by professionals who follow the trajectory of these young individuals. It is necessary to allow a space in which the adolescents can reflect and find support regarding issues related to the construction of their sexuality and care of one's own body.